2021
DOI: 10.3390/jmse9080813
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Underwater Connectors

Abstract: Underwater connectors are very essential and complex components of deep-sea engineering equipment and their design and manufacture have apparent multidisciplinary characteristics. Wet-mateable connectors (WMCs) represent the highest level of technology in this field, and only a very few countries in the world can produce WMCs. So, WMCs are likely to be a constraining factor to some maritime powers that might try to achieve breakthroughs in this field, constraining the innovation-driven development of deep-sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…These connectors are a reliable and efficient method for transferring power to UUVs, and are more established than UWPT. However, these are complex to manufacture and operate, leading to higher costs and maintenance requirements [46], and are susceptible to corrosion [47].…”
Section: Wet-mate Connectorsmentioning
confidence: 99%
“…These connectors are a reliable and efficient method for transferring power to UUVs, and are more established than UWPT. However, these are complex to manufacture and operate, leading to higher costs and maintenance requirements [46], and are susceptible to corrosion [47].…”
Section: Wet-mate Connectorsmentioning
confidence: 99%
“…One of the most crucial mechanical components for the exploitation of undersea oil resources is offshore production system, which consists of submarine pipelines and their connectors [1,2]. One of the key components in the leakage of offshore oil production equipment is offshore flange connector, which mainly serves to divert offshore oil pipelines and repair pipeline ruptures, and it is mainly comprised of flange, lenticular gasket, and bolt [3,4]. The offshore flange connector is often used for submarine pipeline connection at a water depth of about 500 meters, where most of the connections of offshore flange connectors are directly controlled by divers, or offshore sealing chamber is used as a workspace to connect undersea working machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al studied the influence of flight height on the performance of an aviation electrical connector, and found that its contact force and resistance decrease with the increase of flight altitudes (<10 000 m) 10 . Song et al and Remouit et al investigated the mechanical performance of underwater electrical connectors at different pressures and found that their insertion and extraction forces enlarge with the increase of pressure 11,12 . Ni et al investigated the effect of temperature on insertion and exaction forces in an industry electrical connector, and found that their maximum values increase as increasing temperature 13 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Song et al and Remouit et al investigated the mechanical performance of underwater electrical connectors at different pressures and found that their insertion and extraction forces enlarge with the increase of pressure. 11,12 Ni et al investigated the effect of temperature on insertion and exaction forces in an industry electrical connector, and found that their maximum values increase as increasing temperature. 13 Feng et al studied the influence of vibration on contact forces, and the results indicated that the vibration frequency has little effect on insertion force.…”
mentioning
confidence: 99%